HUBUNGAN PENGELOLAAN SAMPAH DENGAN KEJADIAN DIARE DI KELURAHAN ARGASUNYA KOTA CIREBON - Jaenudin; Sandi Aprianto; Citra Setyo Dwi Andini (Jurnal Kesehatan Mahardika, 2018)
Background: Garbage is something material or solid objects that is no used by humans. The impact or risk of improper handling of garbage can cause to environmental damages that can cause health problems and disesase, one of them is diarrhea disease. According to the health profile of West Java Province (2012) showed that the 1.906.886 diarrhea incidence. Cirebon City is ranked ninth with 88,702 diarrhea incidence. Purpose: The purpose of this research is to know the relationship of waste management with the incidence of diarrhea In Argasunya Village Cirebon City. Method: This research used descriptive correlation with kohort retrospekif approach. The population in this study that is all the people who suffer from diarrhea in the Argasunya Village with 72 respondents. The sample in this study using total sampling with 72 respondents who suffer from diarrhea. The research instrument used the observation sheet of waste management and the result of the status of the patient according the medical record data in Sitopeng Public Health Center. The analysis used univariate and bivariate used Chi Square test. Result: The result of univariate analysis showed that most of the waste management did not fulfill the requirement of 59 respondents (81,9%) and most of the acute diarrhea was 62 respondents (86,1%). There was no significant relationship of waste management with the incidence of diarrhea In Argasunya Village Cirebon City, p-value = 0,677.